Istical Characterization of Aerosols’ Liquid Water Content and Visibility for Terrestrial FSO Links - Khan, Muhammad Saeed; Nebuloni, Roberto; Grabner, Martin; Capsoni, Carlo; Leitgeb, Erich; Kvicera, Vaclav (Communications - Scientific letters of the University of Zilina, 2012)
Liquid water content (LWC) is a microphysical parameter which is used to characterize fog/cloud and other particulates. In the absence of precipitation higher amount of LWC depicts dense fog, significantly reducing visibility and causing performance degradation of free-space optical (FSO) links for a non-negligible amount of time. A measurement campaign in Prague (Czech Republic) has recorded the specific attenuation caused by fog in terrestrial FSO links along with visibility, liquid water content (LWC) and integrated particle surface area (PSA) for operational wave-lengths of 1550 nm and 830 nm (installed at two different path links). This contribution presents and analyzes 5 months real time measured data of LWC and visibility for terrestrial FSO links in an attempt to find the best fit distribution model for aerosol’s liquid water content and visibility for terrestrial FSO links under reduced visibility conditions. The Probability Density Function (PDF) estimation of visibility and LWC puts forth the Gamma distribution as the best fit distribution for both. The results provide the statistical behaviour of LWC and visibility, which is of high importance for Optical Wireless systems and networks.